THE REALITY OF TESTAMENT IS ON THE LEGISLATION OF UKRAINE, LITHUANIA AND POLAND - Mankovskyi, Volodymyr (Global Prosperity, 2021)
One of the primary vectors of the development of probate law in any developed state is providing the proper will of the person in case of own death, i.e. drafting of testament. As with any legal transaction, for the generation of corresponding legal relationships, a testament must be actual, i.e. perfect on condition of observance of all legislation requirements. Invalidation of a will is a tool that allows regulating the form of expression of the testator’s will. It sets limits on the content of testamentary dispositions regarding their legality, which, in turn, ensures respect for the rights and interests of heirs. This research touches on the analysis of the reality of testament on the legislation of Ukraine, Lithuania, and Poland, as the nearby states with the alike legal system, in the cut of grounds for subsuming of testament invalid or insignificant (Ukraine) legal transactions.